THE ROLE OF AUDIO GAMES IN EARLY FOREIGN LANGUAGE EDUCATION - Rozieva Malika Mamedzhanovna; Zhumabekova Galiya Baiskanovna; Bainesh Sholpan Borantaikyzy (Foundations and Trends in Modern Learning, 2025)
This article examines the pedagogical role of audio games in early foreign language learning by integrating several theoretical perspectives, including Bruner’s constructivism, Vygotsky’s sociocultural theory, Russian pedagogical traditions, and Kunanbayeva’s communicative-cognitive approach. The study synthesizes theoretical literature and contemporary methodological sources to analyze how audio games support auditory perception, phonological awareness, vocabulary development, listening comprehension, and communicative competence in young learners. The analysis demonstrates that audio games align with children’s psychophysiological characteristics—such as heightened auditory sensitivity, emotional responsiveness, and a natural preference for play—while also providing structured scaffolding that enables gradual linguistic development. The findings indicate that audio games contribute to cognitive activation, motivation, and interactional engagement, offering developmentally appropriate ways to integrate sound-based instruction into the primary foreign language classroom. The article concludes that audio games constitute an effective, theoretically grounded, and pedagogically meaningful method that enhances the quality of early foreign language education and supports national and international trends toward communicative, child-centered instruction